Nursing of a case of hyperemesis gravidarum treated by acupoint pressing combined with acupoint application (穴位按压联合穴位贴敷治疗妊娠剧吐1例护理体会) - DU Minjie (杜敏杰); DU Yun (杜云); YIN Qi (殷琪); SU Huilin (苏会琳) (Association of Integrative Nursing, 2023)
This paper summarized the nursing management for a case of hyperemesis gravidarum treated by acupoint pressing combined with acupoint Application of Traditional Chinese Medicine (TCM). Key issues of nursing mainly included acupoint selection, pressing technique, Chinese herbal medicine ointment making and precautions during treatment. In addition, life guidance, diet care, social support and psychological intervention were carried out jointly to reduce the frequency of vomiting and improve patient's quality of life. (本文总结穴位按压联合中药穴位贴敷治疗1例妊娠剧吐患者的护理经验, 主要包括取穴、穴位按压、中药药膏调制以及注意事项等, 同时配合生活指导、饮食调护、社会支持、心理干预等护, 减少患者呕吐次数, 提升患者生活质量。)